Exercise and Physical Activity in the Therapy of Substance Use Disorders - Elisabeth Zschucke; Andreas Heinz; Andreas Ströhle (2012)
Exercise and physical activity are constantly gaining attention as adjuvant treatment for substance use disorders, supplementing classical pharmacological and psychotherapeutic approaches. The present work reviews studies addressing the therapeutic effects of exercise in alcohol abuse/dependence, nicotine abuse/dependence, and illicit drug abuse/dependence. In the field of smoking cessation, evidence is strong for exercise as an effective adjuvant treatment, whereas no generalizable and methodologically strong studies have been published for alcohol and drug treatment so far, allowing only preliminary conclusions about the effectiveness of exercise in these disorders. A couple of potential mechanisms are discussed, by which exercise may act as an effective treatment, as well as future directions for studies investigating exercise as a treatment strategy for substance use disorders.